Pengembangan Model Manajemen Pendidikan Berbasis Teknologi Informasi untuk Meningkatkan Kualitas Pendidikan - Nursaman; Ahmad Aris Fajarudin (Universitas Nahdlatul Ulama Pasuruan, Indonesia, 2025)
Abstract Purpose: This research aims to develop an information technology-based educational management model to improve education quality in the digital era. Digital transformation in education demands a paradigm shift in management that integrates information technology across all aspects of educational institution governance. Design/methodology/approach: This study employs a qualitative approach with case study methods in several educational institutions that have implemented IT-based management systems. Data collection was conducted through in-depth interviews, observations, and document analysis. Research limitations/implications: This research provides theoretical contributions in developing modern educational management concepts and practical implications for educational institutions in designing sustainable digital transformation strategies. Findings: The results show that an effective IT-based educational management model includes five main components: technology infrastructure, integrated management information systems, digital competency development, IT policies and governance, and continuous evaluation. Implementation of this model has proven to increase administrative efficiency, learning effectiveness, information accessibility, and data-driven decision making. Originality/value: This study fills the gap by providing an integrative framework that explains how information technology can enhance management quality and ultimately education quality through a holistic approach considering technical, organizational, and human aspects simultaneously.